Clinicopathological features and endoscopic characteristics of inverted sessile serrated adenomas/polyps - Takashima, Kenji; Oono, Yasuhiro; Kojima, Motohiro; Ikematsu, Hiroaki; Akimoto, Tetsuo; Yano, Tomonori (Endoscopy International Open, 2019)
Background and study aims This study was designed to clarify clinicopathological, endoscopic, and genetic characteristics of inverted sessile serrated adenomas/polyps.Patients and methods In this retrospective study, we reviewed the pathology reports of patients treated in our hospital between January 2010 and June 2015 and identified sessile serrated adenomas/polyps that were diagnosed with endoscopic resected specimens. Clinicopathological, endoscopic, and genetic features were compared between the inverted and ordinary types.Results Among the 104 sessile serrated adenomas/polyps, 37 lesions were inverted (35.6 %). The inverted types had two patterns of invasion: expansive and infiltrating growth. Expansive growth was observed in 15 cases (40.5 %) and infiltrating in 22 (59.5 %). Regarding the clinicopathological findings and endoscopic characteristics of the inverted types, presence of adherent mucous, location in the right-side colon, an expanded type-II pit pattern, irregularly dilated vessels, and a depression were demonstrated in 89 % (33/37), 73 % (27/37), 54 % (20/37), 75 % (28/37), and 35 % (13/37), respectively. Contrastingly, these were demonstrated in 86 % (58/67), 84 % (56/67), 55 % (37/67), 58 % (39/67), and 0 % (0/67), respectively, in the ordinary type. In the univariate analysis, male sex and a depression in the adenoma/polyp were significantly associated with inverted types (P < 0.001). BRAF mutation at codon 600 was found in six of seven ordinary types and in 11 of 11 of the inverted types. KRAS, NRAS, and PIK3CA mutations were not found in the ordinary and inverted types.Conclusion More than 30 % of sessile serrated adenomas/polyps were pathologically diagnosed as inverted, and approximately 40 % of them were of the expansive growth type and easily diagnosed with endoscopy.